2005
DOI: 10.1080/14034940410028406
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in the general population: A translation and test of the psychometric properties of the Norwegian version of the fatigue severity scale

Abstract: The psychometric properties of the Norwegian version of FSS were satisfactory. To avoid over-diagnosing people for high level of fatigue, the threshold for high fatigue probably should be 5 on the FSS scale instead of 4 as had been suggested originally, but further validation of the cut-off point is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
280
2
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(317 citation statements)
references
References 30 publications
29
280
2
6
Order By: Relevance
“…Several other studies have reported higher prevalences of fatigue in women than in men (4,(12)(13)(14)(15)(16). A cross-sectional Danish population study in a random age-stratified sample of 16-77-year-old persons showed that, on average, there was not much difference in fatigue between men and women, but that there was an excess of women among persons with very high levels of fatigue (17).…”
Section: Introductionmentioning
confidence: 93%
“…Several other studies have reported higher prevalences of fatigue in women than in men (4,(12)(13)(14)(15)(16). A cross-sectional Danish population study in a random age-stratified sample of 16-77-year-old persons showed that, on average, there was not much difference in fatigue between men and women, but that there was an excess of women among persons with very high levels of fatigue (17).…”
Section: Introductionmentioning
confidence: 93%
“…at least 5 defined as severe fatigue, 25 and has demonstrated test-retest reliability of kappa=0.74 for the average score. 26 Body structure ⁄ function Foot deformity, defined as tibiocalcaneal angle being greater than 5°varus or valgus, was determined by visual categorization with the participants in standing position.…”
Section: Activity ⁄ Participationmentioning
confidence: 99%
“…24 Fatigue was measured with the Fatigue Severity Scale, a questionnaire using a scale from 1 to 7. 25 The questionnaire is validated in the Norwegian population, with average scores of What this paper adds…”
Section: Activity ⁄ Participationmentioning
confidence: 99%
“…Опросник The 7-item Fatigue Severity Scale (FSS-7), обладающий хороши-ми психометрическими показателями среди взрослых пациентов с различными заболевани-ями, применяли для оценки усталости [16]. The American knee Society Score и Function Score (kSS) были использованы для оценки функции коленного сустава [10].…”
unclassified